Challenging the Female Stereotypes in Indian Television Advertisements: The Women Consumers’ Perspective - Raychaudhuri, P. S. (Indian Journal of Marketing, 2014)
The stereotypical roles portrayed by women in advertisements have been a matter of much public criticism and controversy. Their submissive and exploited image has cast a negative impact on the women’s community all over the world as researched by different scholars with more emphasis on content analysis techniques of advertisements. However, this empirical research - conducted among women consumers like housewives and modern girls/ working women residing in a cosmopolitan city - Delhi - discusses about their attitudes, reactions, and perceptions about the two major role stereotypes in Indian television advertisements, that is, submissive roles for housewives advertising household products and glamorous roles for modern girls advertising cosmetic products with examples. The paper also analyses certain hypotheses (whether the consumers would agree to a role reversal in these cases), examines the bias of the advertisers towards fair skinned models for cosmetics, and how do these commercials influence the respondents’ purchase intentions, and so forth. The results show that women consumers are influenced by the advertisements for their purchase requirements; however, they not satisfied with the stereotypical nature of role portrayal and the bias towards fair skin in TV advertisements, and would welcome a reversal of roles for housewives and modern girls respectively. They would prefer an average Indian woman with dusky skin color in different advertisements; a point that could help marketers design their promotional strategies.